Hepila vs. Hesperia: The Linguistic Controversy in Don Quixote of 1605 Solved by LLMs? - Rodríguez, Elio Quiroga (Cervantes, 2026)
In the first edition of Miguel de Cervantes's El ingenioso hidalgo don Quijote de la Mancha, published in 1605, the phrase "por Hepila Famosa" appears, the meaning of which has been the subject of controversy. This study analyses the context of the phrase and proposes five possible interpretations, assessing the probability of each. The hypotheses include the possibility of a typographical error, a reference to a fictitious place, an allusion to an unknown real place, the use of an archaic term, and a possible interpretation as a forgotten character. It is concluded that the most likely explanation is a typo, possibly "por Hesperia famosa" or "por Hispania (Hesperia) famosa," given the poetic context and Cervantes's common practice of using lofty names to allude to Spain.